2008
DOI: 10.1002/uog.5330
|View full text |Cite
|
Sign up to set email alerts
|

Non‐influence of fetal gender on ductus venosus Doppler flow in the first trimester

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous work investigated the influence of fetal sex on DV PIV and PVIV during the first trimester. The clinical findings in healthy pregnancies were heterogeneous with DV PIV found to be elevated in females in one study [37] and not statistically different between females and males in another [38]. More recently, the Trial of Umbilical and Fetal Flow in Europe (TRUFFLE) reported assessment of the DV throughout gestation, combined Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work investigated the influence of fetal sex on DV PIV and PVIV during the first trimester. The clinical findings in healthy pregnancies were heterogeneous with DV PIV found to be elevated in females in one study [37] and not statistically different between females and males in another [38]. More recently, the Trial of Umbilical and Fetal Flow in Europe (TRUFFLE) reported assessment of the DV throughout gestation, combined Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The papers on uterine artery Doppler prediction of pre‐eclampsia and fetal growth restriction are probably non‐controversial from a safety point of view, because the fetus is not insonated during the Doppler examination. However, among the seven papers on fetal Doppler at 10–14 weeks6–12, only one6 appeared explicitly to fulfil the requirements listed by the Journal Editors in 19995. (We don't know that the others didn't, we just know that they did not obviously do so.)…”
Section: Journal Policy On Publishing Reports Of First‐trimester Doppmentioning
confidence: 99%